Melanotic Neuroectodermal Tumor of Infancy: the Use of Immunohistochemical Analysis - André Luca Araujo de Sousa; Wanderson Carvalho de Almeida; Jean de Pinho Mendes; Victor Angelo Martins Montalli; Antonione Santos Bezerra Pinto (University of Zagreb. School of Dental Medicine, 2022)
The Melanotic Neuroectodermal Tumor of Infancy (MNTI) is an asymptomatic, pigmented neoplasm characterized by a fast and locally aggressive growth along with a rare tissue formation. In the diagnostic process, the use of imaging exams can suggest a local destruction suggestive of malignancy, a sign of bone remodeling and expansion. Therefore, as any early diagnosis minimizes risks and improves the prognosis of treatment for the patient, the aim of this study was, based on a clinical case report, to corroborate the use of histopathological analysis associated with immunohistochemistry. Thus, we conclude that the immunohistochemical exam is of great importance for a better complementation of the MNTI diagnosis process. In addition, it can reveal signs of possible aggressive growth.